Comparative effects of biocontrol agent and pathogen on Nicotiana tabacum: insights into fungal-plant interactions - Quanyu Yin; Zhichao Ren; Dongling Wu; Zhao Feng; Zhengkang Zhu; Amit Jaisi; Hui Wang; Mengquan Yang (Plant Signaling & Behavior)
Tobacco (Nicotiana tabacum) black shank disease, caused by Phytophthora nicotianae, is a significant threat to tobacco crops, leading to severe economic losses. Prolonged use of agrochemicals to control this disease has prompted the exploration of eco-friendly biological control strategies. This study investigated the effects of Trichoderma harzianum, a biocontrol agent, on N. tabacum in comparison to P. nicotianae, focusing on growth, biomass, root morphology and anatomy, hormonal changes, and osmotic regulation. T. harzianum significantly enhanced plant growth, biomass accumulation, root system development, and physiological attributes such as photosynthetic pigment levels and antioxidant enzyme activity. In contrast, P. nicotianae negatively impacted these parameters, inhibiting growth and physiological function. Notably, T. harzianum increased proline content and enhanced induced resistance mechanisms, mitigating stress and promoting overall plant health. These findings highlight the potential of T. harzianum as a sustainable solution for managing black shank disease while improving tobacco crop productivity.